Adapted Volt-VAr Extremum-Seeking Method for Voltage Regulation and Loss Minimization in Low Voltage Distribution Networks - J. H. S. Carvalho; W. M. Dos Santos; A. R. Almeida; B. F. S. Junior (IEEE Access)
The high penetration of Distributed Generation (DG) in the low-voltage distribution grid has raised several concerns in recent years, mainly regarding overvoltage at the buses caused by the reversal of active power flow. In order to solve this problem, this work proposes an adaptation of the Volt-VAr Extremum-Seeking (Volt-Var-ES) method, which, in addition to promoting voltage regulation, also minimizes active losses in the network. This approach is framed within the concept of local Volt-VAr control since it requires only local measurements and does not depend on an accurate grid model. The IEEE European Low Voltage Test Feeder was used as the test network, with some adaptations to bring it closer to the Brazilian reality. The adapted method was applied in several allocation scenarios and at different levels of DG penetration, and its results were compared with those of the conventional Volt-VAr method, presented in IEEE 1547:2018. The simulations showed that the adapted Volt-VAr Extremum-Seeking method satisfactorily regulates the grid voltage and reduces active losses compared to the conventional Volt-VAr, generating financial savings for utilities and avoiding financial losses for photovoltaic (PV) system owners due to active power curtailment.